KITYKAT
contestada

Combine similar terms and apply the operation. Do NOT evaluate or simplify.
1) 2x + 4 + 3x
2) 12 + 5x -8
3) 2x^2 + 3x^2 + 4x
4) 5ax - 12 - ax
5) 4xy + 2x + 3xy + x

Respuesta :

1. 2x+ 4+3x
= (2x+ 3x)+ 4

2. 12 + 5x -8
= 5x + (12-8)

3. 
2x^2 + 3x^2 + 4x
= (2x^2+ 3x^2)+ 4x

4. 
5ax - 12 - ax
= (5ax -ax) -12

5. 
4xy + 2x + 3xy + x
= (4xy+ 3xy)+ (2x+ x)

Hope this helps~

Answer:

1. 2x+ 4+3x

= (2x+ 3x)+ 4

2. 12 + 5x -8

= 5x + (12-8)

3. 2x^2 + 3x^2 + 4x

= (2x^2+ 3x^2)+ 4x

4. 5ax - 12 - ax

= (5ax -ax) -12

5. 4xy + 2x + 3xy + x

= (4xy+ 3xy)+ (2x+ x)

Step-by-step explanation:

mark me brainlist plzz